Effective extraction of carotenoids from brown seaweeds and vegetable leaves with edible oils. (March 2020) - Teramukai, Kazuyoshi; Kakui, Shusuke; Beppu, Fumiaki; Hosokawa, Masashi; Miyashita, Kazuo
Abstract: Factors affecting carotenoid extraction with edible oils were examined using edible brown seaweed, Sargassum horneri, as main sample. The results indicate that drying was essential to extract fucoxanthin (Fx) from S. horneri and physical (boiling) and chemical (acid/alkali) pretreatment of the wet sample increased the extraction rate of Fx. Additionally, more Fx was found from the dried S. horneri powder with a smaller particle size. The extraction rate of Fx is affected by the extraction temperature and time, showing that the effective extraction would be obtained at 50 °C within 12 hr extraction. Among the oils used, short-chain (C4 and C6) triacylglycerol (TAG) (SCT) and medium-chain (C8) TAG (MCT) could extract more Fx from S. horneri and more β-carotene and lutein from spinach and olive leaves. The relatively lower viscosity of SCT and MCT would be the most likely reason for the higher extraction rates of both TAGs. Graphical abstract: Unlabelled Image Highlights: The present study shows that carotenoids can be effectively extracted by edible oils. Drying was essential to extract carotenoids with edible oils. Physical (boiling) and chemical (acid/alkali) pretreatment increased the extraction rate of carotenoids. Medium-chain triglycerides (MCT) could extract more carotenoids from natural resources. The oil extract of MCT can be applied as functional food material.